Analisis Yuridis Penerapan Nominee Share Agreement Berdasarkan Pasal 33 Undang-Undang Nomor 25 Tahun 2007: Studi Putusan Pengadilan Tinggi DKI Jakarta Nomor 375/Pdt/2018 - Rosa P.S. Simarmata; Ningrum Natasya Sirait; Mahmul Siregar (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Legal certainty in the preparation of Sale and Purchase Deeds (AJB) by Land Deed Officials (PPAT) is a crucial aspect in ensuring the validity of land rights transfers. This study examines Certificate of Ownership No. 710/Kuta Village based on the Denpasar High Court Decision No. 35/PDT/2021/PT DPS using a normative juridical method and statutory approach. The results indicate that violations of formal requirements by PPAT result in the deed being declared invalid and undermine legal certainty. Furthermore, PPAT liability includes both administrative and civil aspects, making compliance with legal procedures essential to ensure the validity and legal certainty of a deed.